2016
DOI: 10.4148/2637-4552.1040
|View full text |Cite
|
Sign up to set email alerts
|

Improving Reflection during Student Teaching with Technology

Abstract: The process of tapping into the power of reflection is a difficult process for many student teachers to accomplish. Multiple factors hinder the process of reflection in novice teachers. Video recorded lessons provide a contextualized focus for reflection on specific pedagogical skills. This study conducted by an undergraduate student during the student internship demonstrates the value of utilized video recorded lesson to assist in the development of one student's journey toward becoming a reflective practitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…As the education process progresses, it may be suggested that the education sector gradually adopt e-assessment, as indicated by (Adenuga et al, 2019). When it comes to presenting outputs of performance tasks, students' creativity and reflective practice are activated when they present it on a different platform, such as TikTok in this study, which is in video format (Allen et al, 2016), because they can easily review where they made mistakes and where they can improve. To remain relevant and competitive with other countries, the Department of Education should continuously support educators in creating relevant strategies for 21st-century learners.…”
Section: Discussionmentioning
confidence: 97%
“…As the education process progresses, it may be suggested that the education sector gradually adopt e-assessment, as indicated by (Adenuga et al, 2019). When it comes to presenting outputs of performance tasks, students' creativity and reflective practice are activated when they present it on a different platform, such as TikTok in this study, which is in video format (Allen et al, 2016), because they can easily review where they made mistakes and where they can improve. To remain relevant and competitive with other countries, the Department of Education should continuously support educators in creating relevant strategies for 21st-century learners.…”
Section: Discussionmentioning
confidence: 97%
“…In 1971, the National Student Association (NSA) established the National Gay Student Center (NGSC), which was proposed and staffed initially by Warren Blumenfeld; it operated out of the NSA’s offices in Washington, DC (Larsson 1971; “National Student Congress Bows” 1971; “National Student Congress Slates” 1971). The NGSC, which published three issues of a magazine titled InterChange in 1972 and 1973, worked to facilitate communication across the growing network of organizations (Aiken 1972; Blumenfeld 1972a; Blumenfeld 1972b; Laurence 1972; Blumenfeld 2012; Blumenfeld, pers. comm 2020) 4 .…”
Section: Lgbt Student Organizingmentioning
confidence: 99%
“…Taken in sum, Swivl-based lecture capture was identified as being most effective at facilitating instructor reflection and development through watching successive lecture recordings as a practice [10][11], while other researchers recommend Swivl-based lecture capture as an alternative means of supervisor evaluations of teaching [8][9].…”
Section: Hyflex Courses and Swivl-based Lecture Capturementioning
confidence: 93%
“…Swivl-based lecture capture has been explored as a teaching development tool for several years prior to the pandemic. Swivl-based lecture capture has been used to study teacher discourse in the classroom [7]; to facilitate instructor preparation through repeated observations [8][9]); and to improve instructor reflection during pedagogical training [10]. Additionally, because Swivl robots pivot to capture movement, body language, gesture, and facial expression are well captured, which can provide valuable feedback for behavioral analysis, which other disciplines have recently studied as a means of better understanding client interaction and response [11].…”
Section: Hyflex Courses and Swivl-based Lecture Capturementioning
confidence: 99%
See 1 more Smart Citation